Desarrollo de Conocimiento - Sáenz Blanco, Fabiola; Pérez-bustamante Ilander, Guillermo Olavi (Ingeniería, 2001)
The knowledge, is a valuable intangible asset for the organization, for it becomes it necessary to establish administration elements that allow its development and maintenance in the same one, one of these elements it is the work in team that favors the socialization of the knowledge through the setting in practices of the culture, the leadership, the politicians of human resources and the organizational structure.